DIABETES MELLITUS: APPLICABILITY AND EFFECTIVENESS OF THE EDUCATIONAL WORK ADDRESSED TO THE PHYSICAL ACTIVITY IN BEARERS OF THE PROGRAM OF HEALTH IN THE FAMILY (PHF) OF THE MUNICIPAL DISTRICT OF CUITEGI, PB (Fiep Bulletin - online, 2014)
Introduction: The treatment process and control of degenerative chronic diseases no transmissible (DCDNT) dispute of the diabetic's information necessary explanation. The aim of this study is to verify the applicability and effectiveness of the educational work addressed to the physical activity in bearers of diabetes of PHF. The methodology consist of an exploratory and field study, developed with a group of diabetic patients of PHF of the group Roberto Paulino, Cuitegi-PB, residents in this neighborhood that received information through lectures supplied by nurses on the theme Diabetes and Exercise, during the period of 30 days, with procedures in stages: control of capillary glicemy; talks educational about the importance of the physical activity for the diabetic and soon afterwards, it was selected by draw 10 volunteers for application of an interview itinerary semi-structured, of the type form, containing objective questions on the participants' profile, state of diabetes, perception about the physical activity and the diabetic and their complications. The orientations adopted the ethical aspects of the resolution 196/96 of Ministry of Health that treats of the researches with human beings. The statistical analysis plan felt in percentile of frequency. The results found that: 70% were with ages between 50 and 70 years, 50% widowers, 40% retired, 50% receive less from minimum wage, 80% discovered the pathology between 1 to 5 years, 55% present chronicle complications, 80% said that the lecture was excellent and 90% considered them transparent as for the understanding of the effect of the exercise in the treatment, 90% absorbed learning affirming that they would accomplish exercises, the ones that practice exercises became in 50%, and 20% indicate that accomplish domestic tasks, as cleared, to wash clothes, to do fair, etc. Conclusion: The educational work about the applicability and effectiveness addressed to the physical activity in bearers of diabetes is explanatory and it supplies adhesion to the exercises while treatment form for the bearer.